The Correlation Between the Recurrent Aphthous Stomatitis Lesion and Quality of Life Among Productive-Age Patients - Sari, Liza Meutia; Rezeki, Sri; Rambe, Sarinah; Novita, Cut Fera; Herwanda, Herwanda; Fasya, Safira (Dentistry Faculty, 2023)
Background: Recurrent Aphthous Stomatitis (RAS) is an ulcerative disease in oral mucosa. These lesions are usually located on the non-keratinized oral mucosa with the characteristics of recurrent ulcerated lesions and the presence of pain. Some people affected by RAS will have various impacts on speech, swallowing, and chewing functions. Patients with RAS usually experience pain, and this impact greatly affects their quality of life. Objective: This study examined the relationship between RAS and patients' quality of life. Materials and Methods: This study is a cross-sectional observational study. The method of taking the subjects was done using consecutive sampling with 32 subjects. Data collection was carried out with objective and subjective data. Results: A significant relationship exists between RAS and patient quality of life p = 0.044 (Fisher's Exact Test,p0.05). There is a significant correlation between RAS and patient quality of life Spearman's correlation test, significance p0.05) with a value of p = 0.018 with a strength level of a correlation coefficient of 0.415, which means that it has a moderate level and a direction of the correlation is positive. Conclusion: Aspects of social functioning limitation and bodily pain are most influenced by the emergence of RAS lesions. There is a positive correlation between RAS and patients' quality of life.